Sedimentology and Reservoir Potential of Lower Tanjung Sandstone in Martapura, Barito Basin, South Kalimantan - Widada, Sugeng; Prahastomi, Mochammad; Adha, Ikhwannur; Rizky, Aga (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2024)
The Barito Basin in South Kalimantan, Indonesia, is a hydrocarbon-producing basin where the Eocene Tanjung Formation serves as both the primary source rock and reservoir. Despite historical discoveries, recent exploration has faced challenges in identifying high-quality reservoir rocks. This study evaluates the reservoir potential of the Lower Tanjung Formation in the Martapura area using fieldwork and laboratory analyses, focusing on porosity, permeability, and texture and depositional geometry. The formation comprises thick shale with minor sandstone and coal layers, interpreted to be deposited in an estuarine environment. Sandstone layers, 0.2–12 m thick, are limited in lateral extent, forming a narrow "shoestring" geometry. Porosity measurements range from 19.0% to 33.1% (good to very good), with an average of 24%, while permeability varies from 1.5 mD to 105 mD (tight to very good), averaging 29.7 mD. However, primary porosity of the sandstone (3.6–7.2%) is poor, with secondary porosity (3.6–14.8%) dominating, driven by near-surface weathering during uplift. Our study suggests that some sandstone layers exhibit good potential, but the overall reservoir quality is limited due to poor primary porosity and restricted depositional geometry.